PENGARUH PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP KETERAMPILAN KERJASAMA DAN HASIL BELAJAR IPAS SISWA KELAS VI SD MUHAMMADIYAH BANGKALAN, MADURA - Isrotul Sukma; Christina Ismaniati (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study aims to determine the effect of the Team Games Tournament (TGT) cooperative learning model on the cooperation skills and learning outcomes of sixth-grade students of Muhammadiyah Bangkalan Elementary School. This study is a quasi-experimental quantitative study with a pretest-posttest control group design approach. The research location was carried out at Muhammadiyah Bangkalan Elementary School, with the research subjects being sixth-grade students divided into two groups, namely the experimental class that implemented the TGT model and the control class that followed conventional learning. Data collection techniques used learning outcome tests and observations of cooperation skills. Data analysis techniques used were the independent t-test and paired sample t-test to test the differences in results between the experimental and control groups and before and after treatment in the experimental group. The results showed that the TGT cooperative learning model had a significant effect on improving students' learning outcomes and cooperation skills in science learning. The results of the t-test showed a significance value of 0.000 <0.05, which indicated a significant difference between the control and experimental groups and before and after treatment in the experimental group. Keywords: Learning Outcomes; Cooperation; Cooperative Learning; Team Games Tournament; Science